Address to the Board of Governors, September 29, 1969 - McNamara, Robert S. (World Bank, Washington, DC, 2020)
Robert S. McNamara, President of the World Bank Group, discussed the following topics: past progress and future plans for the expansion of the Bank's operations; increased attention for population planning, educational advance, and agricultural expansion; three urgent, interrelated development problems unemployment, urbanization, and industrialization to which the Bank and all other development institutions must direct additional effort; and an approach to the formulation of a strategy for development.